Evaluation of the role of CD56 cells in unexplained recurrent spontaneous abortion - Zain Eldin, Ahmed Kasem Mohamed; Mohammed Sabra, Ahmed Sabra Ibrahim; Negm, Aziza Ali Elsayed (International journal of health sciences, 2021)
Objective: To determine whether peripheral natural killer (NK) cells play a role in recurrent miscarriage by evaluating the percentage of these cells using flow cytometry and comparing it with the percentages in normal multiparous women and women who experienced miscarriage only once. Methods: This case-control study was carried out on a total of 108 women. The study participants consisted of two groups of cases: unexplained recurrent miscarriage cases (n=36) and explained recurrent miscarriage cases (n=36). Additionally, a control group of normal multiparous women or women with only one previous miscarriage (n=36) was included. Detailed clinical assessments, laboratory investigations, and flow cytometry analysis were conducted to collect relevant data. Flow cytometry was used to determine the percentage of CD56+ NK cells in peripheral blood samples. Results: The mean age of the participants ranged from 26.72 to 28.33 years, with no significant difference among the three groups. Parity showed a statistically significant difference, with a higher proportion of nulliparous women in the unexplained abortion group. The number of previous abortions did not differ significantly between the unexplained and explained groups. Among the causes of abortion, endocrine and immunological factors were prominent.